Unraveling the anti-tumor effects of midazolam in non-small cell lung cancer through the lncRNA XLOC_010706/miR-520d-5p/STAT3/autophagy pathway - Jinghua Jiao; Yifang Tang; Lu Ye; Yaru Yang; Zhenghua Liu (Scientific Reports)
Abstract Anesthesia and perioperative management significantly influence long-term outcomes in patients with early and intermediate stage cancer. Midazolam, a commonly used benzodiazepine anesthetic, has shown potential anti-tumor effects. This study aimed to explore the anti-tumor properties of midazolam in non-small cell lung cancer (NSCLC). The anti-tumor effects of midazolam on A549 and H1650 NSCLC cell lines were assessed using CCK-8 assays, colony-forming assays, and the Annexin V-fluorescein isothiocyanate Apoptosis Detection Kit I. Additionally, Transwell assays were conducted in vitro, and subcutaneous tumor models in nude mice were established to assess the anti-tumor effects in vivo. The interaction within the lncRNA XLOC_010706/miR-520d-5p/STAT3 axis was confirmed through dual-luciferase reporter assays, RT-qPCR, and Western blotting. Midazolam significantly inhibited cell proliferation and invasion while inducing apoptosis in A549 and H1650 cells, both in vitro and in vivo, by promoting autophagy (P<0.05). It also down-regulated the expression of lncRNA XLOC_010706 in the tumor microenvironment (P<0.05). Within the signaling pathway, lncRNA XLOC_010706 functioned as a competing endogenous RNA (ceRNA) targeting miR-520d-5p, with STAT3 identified as a functional target gene for miR-520d-5p in NSCLC. Furthermore, lncRNA XLOC_010706 acted as an oncogene, promoting cell proliferation and invasion while inhibiting apoptosis through the miR-520d-5p/STAT3 axis. Midazolam down-regulates the expression of lncRNA XLOC_010706, which acts as an oncogene in NSCLC. The anti-tumor effects of midazolam occur via the lncRNA XLOC_010706/miR-520d-5p/STAT3 pathway, enhancing autophagy in NSCLC. This indicates that lncRNA XLOC_010706 could serve as a novel diagnostic biomarker and therapeutic target for NSCLC patients.